Literature Review: The Effect of Transformational Leadership Style on Hospital Patient Safety Culture - Ummiya Ummiya; Alpan Habibi (CV Media Inti Teknologi, 2025)
Background of study: Patient safety culture is essential for achieving high-quality safe services. Transformational leadership plays a significant role in shaping a work environment that supports safety. Aims and scope of paper: This review aims to identify the forms of transformational leadership and its impact on patient safety culture in hospitals.Method: This study uses a literature review method with a systematic approach based on PICOT. Data were collected from six databases with criteria set for the years 2021-2025, using keywords 'Leadership Style', 'Patient Safety Culture', and 'Hospital', resulting in 10 journals that were analyzed. This study uses a literature review method with a systematic approach based on PICOT. Data were collected from six databases with criteria set for the years 2021-2025, using keywords 'Leadership Style', 'Patient Safety Culture', and 'Hospital', resulting in 10 journals that were analyzedResults: From the screening results, 10 relevant articles were obtained and analyzed. The results of the analysis show that transformational leadership style has a positive impact on patient safety culture through motivation, role modeling, and individual attention. However, its implementation is still hampered by low incident reporting and weak communication. Safety culture also acts as a mediator between leadership and clinical safety practices. Conclusion: This literature review emphasizes that the application of transformational leadership is effective in strengthening patient safety culture. Team support, staff knowledge, and an open reporting system are essential for realizing a sustainable safety culture.